Synthesis, characterization and thermal studies on solid 3-methoxybenzoate of some bivalent transition metal ions - Vallejo, Adriana Cossu; de Siqueira, Adriano Buzutti; Rodrigues, Érica Alvarenga Crespo; Ionashiro, Elias Yuki; Bannach, Gilbert; Ionashiro, Massao (Eclética Química, 2005)
Solid-state M-3-MeO-Bz compounds, where M stands for bivalent Mn, Co, Ni, Cu and Zn and 3-MeO-Bz is 3-methoxybenzoate, have been synthesized. Simultaneous thermogravimetry and differential thermal analysis (TG-DTA), differential scanning calorimetry (DSC), X-ray powder diffractometry, infrared spectroscopy, and chemical analysis were used to characterize and to study the thermal behaviour of these compounds. The results led to information about the composition, dehydration, thermal stability and thermal decomposition of the isolated compounds.